Behavior of piglets in the nursery phase subjected to environmental enrichment - Andrade, Tiago Vieira de; Andrade, Larissa Siqueira; Farias, Leonardo Atta; Sousa, Paulo Henrique Amaral Araújo de; Borges, Laylson da Silva; Santos, Raimundo Nonato Vieira; Lima, Barbara Silveira Leandro de; Barros Junior, Cicero Pereira; Carvalhinho, Sandro Tavares (Revista de Ciências Agroveterinárias, 2019)
Environmental enrichment consists of the enhancement of facilities by means of the necessary environmental stimuli to achieve animal welfare in psychical, physiological, and to improve quality of life conditions. In recent years welfare has been turning into one of the biggest challenges for modern production systems. There is a great pressure from civil society and international market claiming for production systems to respect animal welfare. This increases the need for studies that generate knowledge on how to raise pigs in order to ensure the profitability of the system and the maintenance of the quality of life for these animals. Therefore, the aim of this study was to evaluate the behavior of piglets in nursery phase subjected to environmental enrichment. A total of 12 pigs in the nursery phase were distributed into two treatments (with and without environmental enrichment). The following behaviors were evaluated: standing, laying, exploring, smelling, drinking, eating, idling, digging, defecating, urinating, sitting, walking, vocalizing, biting, playing, and fighting. Piglet behavior was recorded every 10 minutes during six days. Significant differences (p<0.05) between treatments were found for playing, eating and biting. No significant differences (p>0.05) were found for fighting behavior regarding the treatments, days and animals. Animal behavior was affected by the presence of environmental enrichment, which decreased some undesirable behaviors in production systems.